ON THE ISSUE OF CORRECTING THE CONCEPT OF THE POPULATION HEALTH PROTECTION SYSTEM AT THE PRESENT STAGE - Дмитрий Григорьевич Данцигер; Сергей Николаевич Филимонов; Борис Павлович Андриевский; Константин Викторович Часовников (Медицина в Кузбассе, 2021)
The article proposes a correction of the concept of the population health protection system by highlighting the public and individual levels of management. The performance indicators of each of these two systems are different, for the first – these are indicators of «public health», for the second – indicators of the activity of health care facilities and «individual health».